The role of colostrum for the newborn thermogenesis and feeding strategies for calves raised in low temperatures - Silva, Fernanda Lavínia Moura (2018)
Dairy calves require nutrients for maintenance and growth, but in cold weather, the body alters physiologic processes to control body temperature through thermogenesis, which increases its requirements. In this regard, it is important a better understanding of how different feeding managements act in the calf thermogenesis, performance and health when raised in temperatures below thermoneutral conditions. Based on that, two studies were performed. The first study evaluated thermoregulation, performance and blood metabolites in thirty newborn calves fed 10%, 15% or 20% BW of colostrum. At 24h of life, calves were placed in a temperature-controlled chamber at 10ºC for 150 min. After the cold challenge, calves were individually housed in ambient temperature facilities (26.8 ± 5.9°C) until weaning. Calves given 15% or 20% of BW as colostrum exhibited increased thermoregulatory responses during cold challenge and increased immunity responses during preweaning. The second study compared performance and production cost of 75 calves fed milk replacer (MR) or whole milk (WM) and a traditional starter (TS) or an alternative starter (AS) during low environmental temperatures (1.4 ± 9.2°C). Calves were assigned to one of five treatment groups in a 2 x 2 + 1 factorial. The first treatment was a negative control (NC), 4 L/d of MR from d1 to 49; 2L/d of MR from d 50 to 56 of the study and ad libitum TS (commercial texturized ration). The others four treatments were a high rate (HR) of MR or WM (6L/d from d 1 to 7, 8 L/d from d 8 to 35, 4L/d from d 36 to 42, and 2 L/d from d 43 to 49 of the study) and ad libitum AS (cracked corn from d 1 to 21, low protein grower from d 22 to 28, high protein grower from d 29 to 49 of the study) or TS. After weaning, animals were maintained in group hutches in the same environment until 12 weeks of life. Restricted liquid feeding provided higher economic efficiency. However, the final BW was higher for calves fed HRTS. In addition, feeding calves higher volumes of WM increased growth and decreased morbidity. Besides, replacing commercial TS with an AS in high rate of nutrition presented minimal impact on performance.